The Implementation of School Health Efforts in The Elementary Schools of The Country E.G. Sub Regency of Sragen (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
Implementation research is aimed to know the school health program in the District SDN Sambungmacan along with factors inhibiting and supporters. SDN 15 research sites in the District of Sambungmacan, Sragen. Target research on the implementation of the UKS in SDN District of Sambungmacan, Sragen. Data collection methods used were interviews, direct observation, document tracking and documentation. The scientific approach is qualitative descriptive survey. Results of the study is the UKs implementation in 15 districts Sambungmacan SDN can already be implemented but there are still some obstacles in the field of health education, health care, healthy physical environment of the school. The conclusion that the 4 elementary schools in the District Sambungmacan UKS execution has been carried out with all the indicators that support. 11 State Primary School in District Sambungmacan, Sragen implementation of the UKS has been implemented and there are still obstacles, such as: the provision of health education materials for students needs to be improved, health services for students, especially medical examinations (eye, ear) has not been granted. UKS implementation Sambungmacan State Elementary School District of Sragen can be run and implemented in cooperation with health centers, Unit of the Department of Education and parents.